A Meta-Analysis Using Voyant Tools: Digital Transformation and Innovation of Coffee Marketing Management: - - Al Zarliani, Wa Ode (Sang Pencerah: Jurnal Ilmiah Universitas Muhammadiyah Buton, 2025)
Digital transformation has reshaped the marketing landscape across various sectors, including the coffee industry. Changes in consumer behavior, which increasingly rely on technology, have driven coffee businesses to adopt digital-based marketing strategies in order to remain competitive. This study aims to analyze innovations in digital coffee marketing management as well as to identify relevant market trends and segmentation. The research employs a qualitative method with a meta-analysis approach based on text mining. This approach is used to examine and critically analyze previous studies and relevant documents that discuss digital transformation and innovation in coffee marketing management. By utilizing Voyant Tools as an analytical instrument, the study identifies keyword patterns, term frequency, and conceptual interconnections, thereby enabling comprehensive conclusions regarding effective digital marketing strategies and practices. The findings indicate that digital transformation and innovation in marketing management are key factors in strengthening the competitiveness of the coffee industry. The use of digital technology not only expands market reach but also enhances producer–consumer relationships through more interactive, transparent, and sustainable approaches. The integration of digital strategies with local values and sustainability serves as an essential foundation for the growth of the coffee business in the modern era.